The role of aural and visual landscape perception in patient psychology İşitsel ve görsel peyzaj algısının hasta psikolojisindeki rolü - Özdemir, Ayşe; Fenkçi, Melahat Semin (Journal of Human Sciences, 2016)
The aim of this study is to determine positive or negative effects of a nature themed indoor atmosphere on anxiety levels of patients in terms of integrity of aural-visual perception during Thyroid Fine Needle Aspiration Biopsy (TFNAB) procedure. Within the scope of study, clinic setting where TFNAB procedure was performed within Endocrinology Clinic of a private hospital was determined as study field of sample. The study was conducted with 115 patients (58 in experimental group, 57 in control group) based on voluntariness. While a biopsy was performed on experimental group in the clinic room in which sounds of nature (bird, water, wind, etc.) were used aurally and nature themed photographs (water, plants, and mountain) were used visually, a biopsy was performed to control group in routine clinical setting. As a result of study, it was determined that while using nature-related objects in the context of aural and visual perceptions had a positive effect on patient psychology in the case study of TFNAB procedure, anxiety mean scores significantly decreased (p<0.05) after the procedure compared to pre-procedure. It is thought that this study will make contribution as sample study within the context of considering patient psychology in especially non-operative diagnosis and treatment practices. Özet Bu araştırmanın amacı; Tiroid İnce İğne Aspirasyon Biyopsisi (TİİAB) işlemi sırasında, iç mekânda doğa temalı bir atmosfer oluşturulmasını işitsel-görsel algı bütünlüğünde hasta bireylerin kaygı düzeylerine olan olumlu ya da olumsuz etkilerinin belirlenmesidir. Araştırma kapsamında, özel bir hastanenin Endokrinoloji Kliniği bünyesinde TİİAB işleminin gerçekleştirildiği klinik mekân örneklem çalışma alanı olarak belirlenmiştir. Araştırma, gönüllülük esas kapsamında 115 hasta (58 deney grubu, 57 kontrol grubu) ile birlikte yürütülmüştür. Deney grubuna işitsel olarak doğa sesleri (kuş, su, rüzgâr vb. gibi) ve görsel olarak doğa temalı fotoğrafının (su, bitki ve dağ) kullanıldığı klinik odasında biyopsi işlemi yapılırken kontrol grubuna rutin klinik ortamında biyopsi işlemi yapılmıştır. Araştırma sonunda TİİAB örneğinde, işitsel ve görsel algı bağlamda doğa ile ilişkili ögelerin kullanılmasının hasta psikolojisi üzerinde olumlu etkisi olduğu, kaygı puan ortalamalarının işlem sonrasında işlem öncesine göre anlamlı şekilde azaldığı (p<0.05) belirlenmiştir. Bu araştırmanın özellikle ameliyatsız tanı ve tedavi uygulamalarında hasta psikolojisinin dikkate alınması bağlamında örneklem çalışma olarak katkı sağlayacağı düşünülmektedir.